Working less to take care of parents? Labor market effects of family long-term care in Latin America - Marco Stampini; María Laura Oliveri; Pablo Ibarrarán; Diana Londo\~no; Ho June (Sean) Rhee; Gillinda M. James (Inter-American Development Bank (IDB), 2020)
We use data from time-use surveys and the Mexican Health and Aging Study (MHAS) to analyze the relationship between the need to provide family long-term care (LTC) and womens labor supply in four Latin American countries. Descriptive analysis of time-use survey data from Chile, Colombia, Costa Rica and Mexico shows that: (i) women make up 63% to 84% of long-term family caregivers and account for 72% to 88% of total hours of LTC; (ii) consistently across countries, women who provide LTC are less likely to work, and those who do work less hours per week and have a double burden of work and LTC. Multivariate analysis of longitudinal MHAS data shows that, after accounting for both individual and time fixed effects, parents need for LTC is associated with both a significant drop in the likelihood of working (by 2.42 percentage points) and a reduction in the number of hours worked among women ages 5064 who remain employed (by 7.03%). This finding has important implications for gender equality. Also, in a region that is aging faster than any other in the world, social trends (e.g., smaller households with fewer children) make this provision of LTC within the home unsustainable, increasing the need for public policy action.
Keywords: J14; J16; J18; J21; J22; 330; Female labor supply; Long-Term Care (LTC); elderly care; care dependence; time-use surveys; Mexican Health and Aging Study (MHAS); Latin America; Chile; Colombia; Costa Rica; Mexico